Adult-Onset ANCA-Associated Vasculitis in SAVI: Extension of the Phenotypic Spectrum, Case Report and Review of the Literature - Staels, Frederik; Betrains, Albrecht; Doubel, Peter; Willemsen, Mathijs; Cleemput, Vincent; Vanderschueren, Steven; Corveleyn, Anniek; Meyts, Isabelle; Sprangers, Ben; Crow, Yanick J.; Humblet-Baron, Stephanie; Liston, Adrian; et al. (Frontiers in Immunology, 2020)
STING-associated vasculopathy with onset in infancy (SAVI) is an autosomal dominant disorder due to gain-of-function mutations in STING1 initially. Since its initial description, a wider spectrum of associated manifestations and disease-onset has been observed. We report a kindred with a p.V155M mutant in STING1 with isolated adult-onset ANCA-associated vasculitis in a 19-year-old patient. The father suffered from childhood-onset pulmonary fibrosis and renal failure attributed to ANCA-associated vasculitis, and died at the age of 30 years due to respiratory failure. In addition to this novel presentation of SAVI, an overview of the phenotypic spectrum of SAVI is provided highlighting considerable variability of presentation with in some cases isolated manifestations and the potential of adult-onset disease.